Media Reporting on Environmental Issues and Its Association with Carbon Emission Disclosure - Alit Bintang, I Dewa Ayu; Ardiana, Putu Agus (E-Jurnal Akuntansi; Vol 35 No 1 (2025), 2025)
This research aims to determine how media reporting and relevant stakeholder groups influence the disclosure of carbon emissions by energy companies listed on the Indonesia Stock Exchange from 2020 to 2022. The study analyzes 72 sustainability reports released by these companies during this period, employing legitimacy theory to interpret the findings. Multiple linear regression analysis was used to evaluate the data. The results indicate that media reporting has a significant positive effect on carbon emissions disclosure, while stakeholder groups have no significant impact. Media coverage compels companies to respond more transparently to public expectations and pressure regarding carbon emissions. In contrast, companies seeking legitimacy from the government may opt to meet only the minimum standards set by regulations. Keywords: Carbon Emissions Disclosure; Energy Companies; Media Reporting; Stakeholder Groups; Legitimacy Theory.